The application of Artocarpus integer seed lectin-M in the detection and isolation of selective human serum acute-phase proteins and immunoglobulins - Hashim, Onn Haji; Ahmad, F.; Shuib, A.S. (2001)
Champedak (Artocarpus integer) lectin-M is a lectin with high specificity and affinity for the core-mannosyl residues of the N-linked oligosaccharides of glycoproteins. We have studied the interaction of the champedak seed lectin with human serum glycoproteins that were resolved by 2-dimensional (2-D) gel electrophoresis. The lectin demonstrated strong interaction with haptoglobin beta chain, orosomucoid, al-antitrypsin, alpha (2)-HS glycoprotein, transferrin, hemopexin, alpha B-1-glycoprotein, and the heavy chains of IgA, IgM and IgG of the human serum. With exceptions of the heavy chains of the immunoglobulins and alpha B-1-glycoprotein, all the other lectin-M-probed glycopeptides are acute-phase proteins. The use of champedak lectin-h l to probe for serum glycoproteins that were separated in a 2-D gel electrophoresis and Western blotting technique may be conveniently applied to analyse the acute-phase and humoral immune responses simultaneously. Subjecting human serum to immobilised-lectin-M affinity chromatography was able to isolate intact haptoglobin, alpha (1)-antitrypsin, alpha B-1-glycoprotein, hemopexin and IgA.